Recent Progress in Copper-Catalyzed Asymmetric Allylic Substitution Reactions Using Organoboron Nucleophiles - Shintani, Ryo (Synthesis, 2016)
Recent progress in copper-catalyzed asymmetric allylic substitution reactions with organoboron nucleophiles is reviewed. Wide availability, high functional group compatibility, and mild reaction conditions are the main advantages over conventional highly reactive organometallic nucleophiles. The use of diboron and silylboron reagents for the synthesis of enantioenriched allylboronates and allylsilanes is also included.1 Introduction2 Chirality Transfer of Enantioenriched Allylic Substrates with Organoboron Nucleophiles3 Enantioselective Allylic Substitution of Achiral Substrates with Organoboron Nucleophiles4 Enantioselective Allylic Substitution of Achiral Substrates with Other Boron-Based Nucleophiles5 Conclusions
Keywords: copper catalyst; allylic substitution; asymmetric catalysis; organoboron; diboron; silylboronate